KEPASTIAN HUKUM TERHADAP PERLINDUNGAN HAK ANAK KORBAN PERCERAIAN - Tektona, Rahmadi Indra (MUWAZAH, 2012)
Abstract : Marriage is one part of the necessities of life that exists in society and also a legitimate institution which is recognized by society and the state. In a marriage relationship, sometimes there will be divorce. Many things may trigger the causes, and usually the victims are children. Rights of children custody often become a problem before or after the divorce. This, becomes the obligations of the parties to protect children's rightsAbstrak : Dalam hubungan pernikahan, kadang-kadang akan ada perceraian. Banyak hal yang dapat memicu penyebab, dan biasanya korban adalah anak-anak. Hak anak asuh sering menjadi masalah sebelum atau setelah perceraian. Ini, menjadi kewajiban para pihak untuk melindungi hak-hak anak.